4th IEEE International Symposium on Electronic Design, Test and Applications (Delta 2008) 2008
DOI: 10.1109/delta.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Validation Environment for Differential Power Analysis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
4
0
4
Order By: Relevance
“…Other leakage models are possible, for instance a leakage model that distinguishes rising transitions and falling transitions has been studied in [45,48], but the results obtained were similar to those obtained with the HD model.…”
Section: Hamming Weight Vs Hamming Distance Modelsmentioning
confidence: 56%
“…Other leakage models are possible, for instance a leakage model that distinguishes rising transitions and falling transitions has been studied in [45,48], but the results obtained were similar to those obtained with the HD model.…”
Section: Hamming Weight Vs Hamming Distance Modelsmentioning
confidence: 56%
“…Finally, the acquired tracks are parsed and edited to be compliant with the software for the DPA analysis realized [7] -CASE A 0x32 0x43 0xf6 0xa8 0x88 0x5a 0x30 0x8d 0x31 0x31 0x98 0xa2 0xe0 0x37 0x07 0x00 .. 0xFF by the authors of [6].…”
Section: Setupmentioning
confidence: 99%
“…Figure 9 where K x is assumed to be the correct key, the one actually used during ciphering. Concerning the proposed architecture, we performed DPA on the base AES architecture and on the proposed redundancy-based solution using an in-house DPA simulator [12]. We found that the DPA attack is slightly more difficult to perform on the proposed architecture including one additional RSMA block and comparison circuitry.…”
Section: Differential Power Analysismentioning
confidence: 99%